2019
DOI: 10.1007/s12520-019-00784-w
|View full text |Cite
|
Sign up to set email alerts
|

Plant processing in the Late Mesolithic Poland: in search for function of the mysterious ‘curved knives’

Abstract: Studies on the treatment and use of plants in the Mesolithic are difficult due to the small number of sources. However, they are important because it was one of the basic branches of the economy of the early Holocene community. This article presents the results of use-wear and experimental studies aimed at the interpretation of the function of the so-called curved knives. These tools are associated with the treatment of silica plants, but their actual function is not fully understood. The research was based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Analyses of microwear on flint artefacts from the Rotterdam-Yangtzehaven site (Niekus et al 2015) showed that a large number of tools were used to work wood, bark, and plants with a high silica content. While tools were probably used to make wood and bark artefacts, in the case of plants, as demonstrated by experiments (Osipowicz 2019), it is hard to determine whether a tool was used to make artefacts, or simply to gather and prepare the plant for consumption. Similar observations also refer to artefacts with evidence of working in wood and processing plants recorded in the Mesolithic assemblage from Smolno Wielkie 2 (western Poland), analysed in its functional aspect (Winiarska-Kabacińska 2019).…”
Section: Comparing Results Of the Functional Analysismentioning
confidence: 99%
“…Analyses of microwear on flint artefacts from the Rotterdam-Yangtzehaven site (Niekus et al 2015) showed that a large number of tools were used to work wood, bark, and plants with a high silica content. While tools were probably used to make wood and bark artefacts, in the case of plants, as demonstrated by experiments (Osipowicz 2019), it is hard to determine whether a tool was used to make artefacts, or simply to gather and prepare the plant for consumption. Similar observations also refer to artefacts with evidence of working in wood and processing plants recorded in the Mesolithic assemblage from Smolno Wielkie 2 (western Poland), analysed in its functional aspect (Winiarska-Kabacińska 2019).…”
Section: Comparing Results Of the Functional Analysismentioning
confidence: 99%
“…Regarding other niche construction activities, we suggest that plant manipulation and control of animal presence were common activities for Neanderthals and Mesolithic populations, because charred plant microfossils, stone tools with evidence of plant manipulation (e.g. from the Middle Paleolithic site of Payre in France; Hardy & Moncel, 2011;Osipowicz, 2019), plant microremains from dental calculus (e.g. Cristiani et al, 2016;Henry et al, 2011Henry et al, , 2014 and large numbers of animal bones accumulated through butchering activities were identified within both Middle Palaeolithic and Mesolithic sites.…”
Section: Discussionmentioning
confidence: 96%
“…Solheim et al, 2018), and some only on plants (e.g. Osipowicz, 2019). Evidence of surface transformation (e.g.…”
Section: Tools As Indicators Of Plant Manipulationmentioning
confidence: 99%
“…Despite numerous experiments (e.g. (Caspar et al 2005;Hurcombe 2008;Jensen 1994;Osipowicz 2019;Vaughan 1985) it remains difficult to ascertain the exact nature of plant processing activities because the range of variation is not yet fully understood and traces from working different kinds of plant materials may appear quite similar. On the contrary, hide scraping and antler working are considered common activities on Federmesser sites (e.g.…”
Section: Activities Tool Use and Hafted Technologiesmentioning
confidence: 99%